Screening of bioprotien production from palm kernel cake by Aspergillus terreus UniMAP AA-1 for fish feed - Zulhellme bin Saidon (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
Lack of protien foods in the world today has become apparent and it is needed from day to day, and competition from the food industry, perticularly the production of animal feed. Bioprotein or single cell protien refers to the microbial cell (primary), which are bred to be a source of protien for animal feed such as fish food. In this study, Palm Kernel Cake used as agricultural wastes are known to have high nutritional value as protien, minerals and vitamins as well as it is cheap. The objective of this study was to investigate the optimum fermentation day for a maximum production of bioprotien content and to screen the interaction between the parameters used, such as temperature, inoculum size and moisture content.